(untitled) (The Research of Medical Science Review, 2024)
Background: Polycystic Ovarian Syndrome (PCOS) is a multifactorial endocrine condition that leads to hyper-androgenism, menstrual irregularities, and numerous cysts which eventually result in infertility. PCOS could be associated with social environmental, hormonal, and genetic factors. Study Objective: This study aimed to investigate the genetic association of SNP rs2414096 in the CYP19A1 and rs743572 in the CYP17A1 genes with PCOS in the local female population of District Bahawalpur. Method: For this case-control association study, 100 patients were ascertained with PCOS, and 50 healthy individuals as controls were enrolled. Furthermore, factors like BMI, and Ferriman–Gallwey (FG) score were also explored. Blood samples of all the participants were drawn, and DNA was extracted and analyzed for polymorphisms of CYP19A1 and CYP17A1 genes by using the tetra ARMS-PCR method. A p-value of less than 0.05 was considered to be significant. Results: There was a significant association between hirsutism, and body mass index (BMI), with PCOS. The genotypic distribution for CYP17A1 showed that the wild-type frequency is significantly higher within PCOS females (68%) and controls (70%) with an odd ratio of 1.068 (Cl: 0.57-1.98). The genotypic distribution for CYP19A1 revealed a high frequency of wild type in patients (67%) and also in the control group (86%) with an odd ratio of 2.625 (Cl: 1.117-6.167). Conclusion: There was no significant difference in the genotypic distribution of CYP17A1 alleles and CYP19A1 alleles between patients and controls. This suggested that CYP17A1 and CYP19A1 polymorphisms are not significantly associated with PCOS in the Bahawalpur population.